The Effect of Religiously Integrated Cognitive Behavioral Therapy on the Psycho-Spiritual Well-Being of People Living with HIV - Jose Leonardo L. Degillo; Lisa Anna M. Gayoles (Philippine Social Science Journal, 2020)
This study determined the effect of Religiously Integrated Cognitive Behavioral Therapy (RCBT) on the psycho-spiritual well-being of people living with HIV (PLHIV). A one-group pretest-posttest design was employed to determine the effect of RCBT on the psycho-spiritual well-being of PLHIV. The Psychological General Well-Being Index (PGWBI) and the Spiritual Well-Being Questionnaire (SWBQ) were used to measure psychological well-being and spiritual well-being, respectively. The intervention was a single session RCBT. The participants were PLHIV from the Philippine Catholic HIV/AIDS Network (PhilCHAN) Western Visayas group. The results of the study revealed a statistically significant increase in the psychological well-being of the PLHIV before and after the RCBT. Although there was an increase in the spiritual well-being of the PLHIV after the RCBT, it was not statistically significant. The findings suggest implications for the inclusion of RCBT in the services provided for PLHIV to improve their psycho-spiritual well-being.